Kaj resničnega lahko povemo o fikcijskih likih? - Nemec, Maja (Analiza (Ljubljana), 2024)
The article discusses how the theory of pretenseand the artefactual theory of fiction work in internal and external talk about fiction, and why both fictional anti-realism and realism run into difficulties. It presents Amie Thomasson's (2003b) solution, which preserves the existence of fictional characters as abstract artefacts, but still adopts pretense into the intrafictional discourse to resolve the ambiguities that arise when using fictional names in different contexts. The problematic nature of de repretense, which requires pretending that an abstract object has concrete properties, is highlighted. If we reject de re pretense and accept de dictopretensein the fictional discourse, we lose the uniformity of the theory and claim that fictional names refer in one part of the discourse but not in the other. The aim of this paper is to suggest that, although it requires a dual use of fictive names, the introduction of pretense into a realist theory of fiction does a better job of explaining our understanding of talk about fiction than anti-realist theories.
Keywords: abstract artefacts; abstraktni artefakti; fiction; fictional discourse; fictional names; fikcija; fikcijski diskurz; fiktivna imena; pretense; pretvarjanje